The Impact of Yellow Leaf Curl Disease Stage During Vegetative and Generative Phases on The Growth and Yield of Curly Red Chili Pepper OR Twist 42 - Syahtian Suprayogi; Nugraheni Widyawati; Maria Marina Herawati (The University of Lampung, 2025)
Curly chili (Capsicum annum L.) is one of the vegetable commodities widely cultivated in Indonesia which has a high selling value. Although it has a high selling value, chili cultivation has many obstacles, one of which is the attack of pathogens that reduce the yield of curly chili, especially yellow curly leaf disease on agricultural land. Yellow curly leaf disease is always found in chili cultivation and is the main production obstacle in Indonesia that reduces the harvest. This study aims to see the impact of yellow curly disease attacks in the vegetative and generative phases on the growth and yield of curly red chili cultivation. The study was conducted from August 2023 to March 2024 using the field observation method from the beginning of growth to harvest. Observations were made by measuring the parameters of plant height, stem diameter, number of branches, number of productive branches, fallen flowers, fruit weight, fruit length and observation of yellow curly disease pathogens. The results of the study showed that attacks of yellow curly disease in the vegetative and generative phases had a significant effect on the growth parameters and yield of curly red chili plants. From the results of the analysis of yellow curly disease attacks in the vegetative phase, the number of fruits and fruit weight were lower, namely 10.90 and 32.04 grams/tree, compared to attacks in the generative phase which produced 24.27 and 77.67 grams/tree. Keywords: Begomovirus, Generative, Vegetative, Whitefly, Yellow curl.